2021
DOI: 10.1002/cncr.33664
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns and survival in patients with early‐onset pancreatic cancer

Abstract: Background Pancreatic cancer is uncommon in patients younger than 50 years, although its incidence is increasing. This study characterizes treatment utilization for early‐onset pancreatic cancer (EOPC) versus average‐age‐onset pancreatic cancer (AOPC) and identifies factors associated with failure to receive treatment. Methods The National Cancer Data Base (NCDB) was queried for patients with EOPC (age < 50 years) or AOPC (age ≥ 50 years) from 2004 to 2016. Multinomial regression was used to compare utilizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 24 publications
2
42
0
Order By: Relevance
“…A recent analysis of 248,634 patients in the National Cancer Data Base (NCDB), a hospital-based database of patients that is not designed to be representative of the US population, found patients with EOPC receive more chemotherapy (38% vs. 29%), surgery (9% vs. 6.9%), chemoradiation (12% vs. 9.2%), and multimodal treatment (21% vs. 15%). This analysis also found that patients with EOPC had a higher one-year overall survival rate across all stages than older patients [ 32 ]. Two single-center reviews of patients with EOPC have also shown differences in the treatment of young patients compared to older patients, with younger patients generally receiving more therapy [ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent analysis of 248,634 patients in the National Cancer Data Base (NCDB), a hospital-based database of patients that is not designed to be representative of the US population, found patients with EOPC receive more chemotherapy (38% vs. 29%), surgery (9% vs. 6.9%), chemoradiation (12% vs. 9.2%), and multimodal treatment (21% vs. 15%). This analysis also found that patients with EOPC had a higher one-year overall survival rate across all stages than older patients [ 32 ]. Two single-center reviews of patients with EOPC have also shown differences in the treatment of young patients compared to older patients, with younger patients generally receiving more therapy [ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 97%
“…The etiology for this lack of treatment is unknown, as single-center analyses of EOPC often do not include information on untreated patients. However, one study suggested that patient insurance status, comorbidity prevalence, proximity to treatment, income, and education level may contribute to lower treatment rates for patients with pancreatic cancer [ 32 ]. Additional evaluation of the population of patients with untreated EOPC is warranted to characterize the reasons for, and barriers to, not pursuing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…82,83 Epidemiology and Risk Factors Among patients with EO-PC compared with AO-PC, there are a higher proportion of males and a higher proportion of non-White, composed of a mix of Black, Asian, and Hispanic individuals. 84,85 Data from the WHO mortality database from 1995 to 1999 also demonstrated a higher incidence of EO-PC in males and found that the highest PC rate ratios were found in Central/Eastern European countries (2.4-4.5 for males and 1.6-4.3 for females). 80 Several other studies have corroborated the male predominance of EO-PC.…”
Section: Treatment Recommendations and Outcomesmentioning
confidence: 99%
“…6,7 Possible reasons cited for the rise in EOPC among non-Hispanic White and Hispanic women include increases in body mass index, increased access to diagnostic imaging, detection of certain histologic subtypes (ie, cystic adenocarcinomas) that are more common in women, 5,6 and sex-based differences in exposure to known or unknown agents and risk factors, including estrogen. 7,8 Using retrospective data from the National Cancer Database, Saadat et al 9 explored treatment patterns for patients with EOPC diagnosed from through 2016. The analysis revealed that nearly 20% of patients with EOPC did not receive any therapy, representing a significant missed opportunity for guideline-concordant care for this historically underrepresented group.…”
Section: A Path Forward For Understanding and Addressing Multifaceted...mentioning
confidence: 99%